Maximizing Developmental Potential and Parenting Patterns in the Married Couples Community of GKI Gejayan Yogyakarta - Anggreany, Yuliana; Helsa; Theresia , Allessandra; Rani Lidiawati, Krishervina; Aurelia, Trisha (Fakultas Psikologi Universitas Pancasila, 2025)
An understanding of parenting has becoming increasingly important, especially within church communities. GKI Gejayan recognizes the significance of parenting in supporting the growth of children and adolescents in a Christian context. This understanding led to developing a community service program titled,